Secretory IgA-Fc alpha receptor interaction modulating phagocytosis and microbicidal activity by phagocytes in human colostrum of diabetics - Franca, Eduardo Luzia; Morceli, Glilciane [UNESP]; Gomes Fagundes, Danny Laura; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Honorio-Franca, Adenilda Cristina (Wiley-Blackwell, 2011)
Franc, a EL, Morceli G, Fagundes DLG, Rudge MVC, Calderon I de MP, Honorio-Franca AC. Secretory IgA-Fc alpha receptor interaction modulating phagocytosis and microbicidal activity by phagocytes in human colostrum of diabetics. APMIS 2011; 119: 710-19.The effects of secretory immunoglobulin A (SIgA) interaction with its specific Fc alpha receptors on colostral phagocytes needs further investigation, especially with respect to diabetic women. Accordingly, we studied the colostrum of hyperglycemic women to assess SIgA interactions with Fc alpha receptors of macrophages as well as the functional activity of these cells. The women were divided for colostrum sampling according to their glycemic status: normoglycemia (N = 51), mild hyperglycemia (N = 23), and diabetes (N = 25) groups. We determined the Fc alpha R expression, the IgA on the surface and the surface-bound IgA in colostrum macrophages. We also evaluated the superoxide release and bactericidal killing of these cells. Colostral phagocytes expressed Fc alpha R, contained IgA on the surface and are able to bind to purified SIgA. The bactericidal activity of colostral phagocytes from the hyperglycemic women was similar to that of normoglycemic only when SIgA was used as opsonin. Addition of a MoAb anti-human Fc alpha receptor resulted in a significant decrease of superoxide release and bacterial killing by macrophages when bacteria were opsonized with purified SIgA, suggesting an interaction between SIgA and Fc alpha R. The stimulatory effects of SIgA on the functional activity of phagocytes therefore protect infants, especially of diabetic women, against intestinal infections.
Keywords: Fc alpha RI; colostrum; phagocytes; diabetes; EPEC; SIgA